Mesosetum aureum (Poaceae: Paspaleae: Arthropogoninae), an annual new species with reddish golden trichomes from the northern South America - Silva, Anádria Stéphanie Da; Ribeiro, André Rodolfo De Oliveira; Reis, Priscila Alves Dos; Buso, Glaucia Salles Cortopassi; Oliveira, Regina Célia De (Phytotaxa, 2025)
A new species, Mesosetum aureum, is here described and illustrated. It is an annual species morphologically related to M. cayennense and M. rottboellioides, but can be recognized by the size of racemes and pedicels, size and pilosity of glumes, and length of lower lemma and upper anthecium. It is found in rocky savannas and humid areas of French Guiana, locally called Inselbergs. Micromorphology of the upper anthecium, conservation status, and comparisons with similar species are provided.